Neuromuscular adjustments to unweighted running: the increase in hamstring activity is sensitive to trait anxiety - Fazzari, Camille; Macchi, Robin; Ressam, Camélia; Kunimasa, Yoko; Nicol, Caroline; Martha, Cécile; Bolmont, Benoît; Sainton, Patrick; Hays, Arnaud; Vercruyssen, Fabrice; Lapole, Thomas; Bossard, Martin; et al. (Frontiers in Physiology, 2023)
Introduction. Originally developed for astronauts, lower body positive pressure treadmills (LBPPTs) are increasingly being used in sports and clinical settings because they allow for unweighted running. However, the neuromuscular adjustments to unweighted running remain understudied. They would be limited for certain lower limb muscles and interindividually variable. This study investigated whether this might be related to familiarization and/or trait anxiety. Methods. Forty healthy male runners were divided into two equal groups with contrasting levels of trait anxiety (high, ANX+, n = 20 vs. low, ANX-, n = 20). They completed two 9-min runs on a LBPPT. Each included three consecutive 3-min conditions performed at 100%, 60% (unweighted running), and 100% body weight. Normal ground reaction force and electromyographic activity of 11 ipsilateral lower limb muscles were analyzed for the last 30 sec of each condition in both runs. Results. Unweighted running showed muscle- and stretch-shortening cycle phase-dependent neuromuscular adjustments that were repeatable across both runs. Importantly, hamstring (BF, biceps femoris; STSM, semitendinosus/semimembranosus) muscle activity increased during the braking (BF: +44 ± 18%, p < 0.001) and push-off (BF: +49 ± 12% and STSM: +123 ± 14%, p < 0.001 for both) phases, and even more so for ANX+ than for ANX-. During the braking phase, only ANX+ showed significant increases in BF (+41 ± 15%, p < 0.001) and STSM (+53 ± 27%, p < 0.001) activities. During the push-off phase, ANX+ showed a more than twofold increase in STSM activity compared to ANX- (+119 ± 10% vs. +48 ± 27, p < 0.001 for both). Conclusion. The increase in hamstring activity during the braking and push-off phases may have accelerated the subsequent swing of the free-leg, likely counteracting the unweighting-induced slowing of stride frequency. This was even more pronounced in ANX+ than in ANX-, in an increased attempt not to deviate from their preferred running pattern. These results highlight the importance of individualizing LBPPT training and rehabilitation protocols, with particular attention to individuals with weak or injured hamstrings.